2018
DOI: 10.1111/1365-2435.13029
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of grazer‐induced vegetation transitions on ecosystem carbon storage in the tundra

Abstract: Large herbivores can control plant community composition and, under certain conditions, even induce vegetation shifts to alternative ecosystem states. As different plant assemblages maintain contrasting carbon (C) cycling patterns, herbivores have the potential to alter C sequestration at regional scales. Their influence is of particular interest in the Arctic tundra, where a large share of the world's soil C reservoir is stored. We assessed the influence of grazing mammals on tundra vegetation and C stocks by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 50 publications
6
50
0
Order By: Relevance
“…), previous reports from the same study site (Ylänne et al. ) and other subarctic areas (Köster et al. , ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…), previous reports from the same study site (Ylänne et al. ) and other subarctic areas (Köster et al. , ).…”
Section: Discussionmentioning
confidence: 56%
“…At the site, a continuous soil organic layer of approximately 4.25 cm is found above the mineral soil layer (Ylänne et al. ). The area is bisected by a pasture rotation fence, been in place at least since 1966, which creates a legal border between the reindeer summer ranges and their migration range.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that whether a transition to another vegetation state in response to grazing increases or decreases soil C sequestration could depend on the type of vegetation that is replaced through grazing (Ylänne et al. ). Heath‐ and shrub‐dominated tundra with mixed B. nana and E. hermaphroditum or Salix willows store carbon in the woody biomass and produce slowly decomposable litter, but also maintain high rates of C cycling via labile C inputs and ectomycorrhizal symbionts that efficiently degrade soil organic matter (De Deyn et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Ylänne et al. ). Sites with historical vegetation transitions could provide a tool for predicting the impacts of ongoing grazer‐induced vegetation transitions on SOM stock because the vegetation transitions at these sites occurred several centuries ago and sufficient time has passed for the slow process of SOM accumulation or loss to be recognizable.…”
Section: Introductionmentioning
confidence: 98%
“…The area experiences a suboceanic climate with an annual precipitation of 935 mm and an annual mean temperature of −0.6°C (gridded data, 2006–2015, Norwegian Water Resources and Energy Directorate, http://www.senorge.no). The mean annual precipitation and temperature in 2013 and 2014 (the years in which this study was performed) were fairly normal for the last decade, but since mean annual temperatures have increased over the last 50 years at a rate of almost 1° per decade, these years were warmer than the long‐term averages (Ylänne, Olofsson, Oksanen, & Stark, ). The study site is divided by a reindeer fence, established in the 1960s to help keep the reindeer within their legal summer ranges.…”
Section: Methodsmentioning
confidence: 96%